2022
DOI: 10.1123/ijspp.2021-0297
|View full text |Cite
|
Sign up to set email alerts
|

Do Race Results in Youth Competitions Predict Future Success as a Road Cyclist? A Retrospective Study in the Italian Cycling Federation

Abstract: Purpose: The aim of this study was to investigate the relationship between youth road cycling success and becoming a professional cyclist. Specifically, the authors sought to analyze (1) the differences in the success scores in youth categories between future professional (PRO) and future nonprofessional (NON-PRO) cyclists, (2) whether relative age effect influences youth road cycling career pathways, and (3) whether youth competition success could predict a future career as a professional cyclist. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Moreover, it suggests that the development of swim performance becomes more stable during the late junior years (males aged 16–17; females aged 15–16), which is in line with previous work of Costa et al (2011) . As such, we state that the importance of performance level increases as swimmers approach their age of peak performance ( Allen and Hopkins, 2015 ), and that a high level of swim performance at late junior age (i.e., being on track), may be required to advance to the senior elite level, which was also observed in other individual sports like cycling ( Gallo et al, 2022 ; Mostaert et al, 2022 ). Additionally, we have found that not all high-performing juniors ended up as high-performing seniors.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, it suggests that the development of swim performance becomes more stable during the late junior years (males aged 16–17; females aged 15–16), which is in line with previous work of Costa et al (2011) . As such, we state that the importance of performance level increases as swimmers approach their age of peak performance ( Allen and Hopkins, 2015 ), and that a high level of swim performance at late junior age (i.e., being on track), may be required to advance to the senior elite level, which was also observed in other individual sports like cycling ( Gallo et al, 2022 ; Mostaert et al, 2022 ). Additionally, we have found that not all high-performing juniors ended up as high-performing seniors.…”
Section: Discussionmentioning
confidence: 92%
“…Within road cycling, competition results are frequently used as the main criterion to identify and select youth cyclists as potential cyclists [4][5][6] . For example, the predictive value of youth competition results from the U17, U19, and U23 category onwards was recently studied and confirmed, with the highest success rates reported in the second year of the categories [5][6][7] .…”
Section: Introductionmentioning
confidence: 87%
“…However, uncertainties persist when considering younger athletes in the junior category. Various studies have suggested a trend toward weaker predictive power in the very early categories, but stronger predictability as athletes approach the U-19 and U-23 categories [8,9,11]. In the context of talent identification in track cycling junior categories, expert coaches, athletes, and former athletes acknowledge the limitations of relying solely on publicly available UCI indicators, especially considering the increased opportunities for showcasing throughout the season offered by a denser competition calendar.…”
Section: Performance Indicators To Predict Future Successmentioning
confidence: 99%
“…While the research focus has primarily centered on road and off-road cycling [8][9][10][11], the past two decades have witnessed numerous endeavors to explore and unveil the potential key factors influencing track cycling performance [2]. However, to date, little attention has been paid to characterizing the success rate of youth talent transitioning to the elite categories and elucidating the performance indicators that unveil their potential in the realm of track cycling [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation